2020
DOI: 10.1177/0265407520903811
|View full text |Cite
|
Sign up to set email alerts
|

Communal coping: A multi-method approach with links to relationships and health

Abstract: Communal coping is defined as the appraisal of a problem as shared and collaboration to address the problem. The goals of the present study were to apply a multi-method approach to (1) disentangle appraisal and collaboration, (2) establish links to relationships and health outcomes, and (3) demonstrate that collaboration mediates the relations of shared appraisal to outcomes. Self-report measures, an observational measure, and we-language were assessed in patients with type 2 diabetes and their spouses ( n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 32 publications
(58 reference statements)
3
40
0
Order By: Relevance
“…Although there is a large and growing literature showing that communal coping is linked to better coping, enhanced relationship well-being, reduced psychological distress, and better physical health (e.g., Van Vleet et al, 2018; Zajdel & Helgeson, 2020) that work has failed to examine causality. The prior work’s strength has been external validity rather than internal validity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there is a large and growing literature showing that communal coping is linked to better coping, enhanced relationship well-being, reduced psychological distress, and better physical health (e.g., Van Vleet et al, 2018; Zajdel & Helgeson, 2020) that work has failed to examine causality. The prior work’s strength has been external validity rather than internal validity.…”
Section: Discussionmentioning
confidence: 99%
“…At Time 2, speakers were asked to indicate how much they agreed with statements ranging from 1 = strongly disagree to 5 = strongly agree: “This task is solely my responsibility”; “This task is as much my friend’s task as it was mine”; and “I was instructed to think of this task as a shared responsibility between me and my friend.” Partners answered the same three questions except the first statement read as: “This task is solely my friend’s responsibility.” These measures were designed for the specific stressor but adapted from previous research (e.g., Zajdel & Helgeson, 2020). Reliability was good for both speaker (α = .85) and partner (α = .89).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, shared appraisal may not be static. For example, one study showed that 39% of the variance in appraisal scores measured daily across 14 days were attributed to within-person fluctuations among patients with type 2 diabetes (Zajdel & Helgeson, in press). Although this finding suggests fluctuations in appraisal exist, the researchers did not specifically study fluctuations or examine their correlates or links to relationship and health.…”
mentioning
confidence: 99%